THE FORDYCE MITCHEL COLLECTION AT THE YALE UNIVERSITY ART GALLERY – PART II - Benjamin HELLINGS (Journal of Ancient History and Archaeology, 2019)
In 2018, the Numismatics department at the Yale University Art Gallery received a donated collection of 223 bronze and silver coins, broadly from the Greek, Hellenistic, and Roman periods. The collection was assembled in the 1950s and 1960s by Professor Fordyce W. Mitchel, a Yale alumnus, and was donated by his three children, Fordyce, Henry, and Magdalen. Prof. Mitchel received numismatic tutelage from the renowned numismatist Alfred R. Bellinger, who at the time served as de-facto curator for the Yale numismatic collection. This article serves to document and highlight the body of material in order to make its existence known to the wider academic community. A catalogue of the coins is includedIn 2018, the Numismatics department at the Yale University Art Gallery received a donated collection of 223 bronze and silver coins, broadly from the Greek, Hellenistic, and Roman periods. The collection was assembled in the 1950s and 1960s by Professor Fordyce W. Mitchel, a Yale alumnus, and was donated by his three children, Fordyce, Henry, and Magdalen. Prof. Mitchel received numismatic tutelage from the renowned numismatist Alfred R. Bellinger, who at the time served as de-facto curator for the Yale numismatic collection. This article serves to document and highlight the body of material in order to make its existence known to the wider academic community. A catalogue of the coins is included and images of the coins are freely available online on the Yale University Art Gallery website. and images of the coins are freely available online on the Yale University Art Gallery website.